高位前交通動脈瘤に対する安全なクリッピング手術: 穿通枝およびHeubner's arteryの温存法 - 池田, 清延; 毛利, 正直; 木嶋, 保; 正印, 克夫 (脳卒中の外科, 2002)
We studied how to minimize the brain retraction and preserve the hypothalamic (hA) and Heubner's artery (HA) in clipping surgeries for high-positioned Acom aneurysms with the pterional (PT), orbitocranial (OC), and interhemispheric (IH) approaches using cadavers and in clinical cases. With the PT approach, excessive retraction of the frontal lobe was required to access Acom aneurysms located higher than 10 mm from the anterior clinoid process. Untethering of the frontal lobe (wide split of the sylvian and IH fissure, opening of the basal cisterns and division of the thick arachnoid fibers from the optic nerves and chiasma, etc.) and a gyrus rectus (GR) resection minimized brain retraction and exposed the Acom complex up to 13 mm high. Subpial GR resection was required to avoid injury of Heubner's artery (HA). Long and excessive retraction of the frontal lobe including the Al and HA should be avoided to prevent subsequent brain infarction. The OC approach offered much wider and better exposure of Acom aneurysms up to 15 mm high. Sacrifice of the olfactory nerve, if possible, offered access to Acom aneurysms higher than 15 mm even with the PT and OC approaches. The IH approach, preferable for high-located and superiorly-posteriorly projecting Acom aneurysms, could not always offer visual access to the hA running behind the aneurysmal dome. In one such case, the hA could be prepared by placing a small rubber sheat between the aneurysmal dome and the hA. In safe clipping surgeries for high-located aneurysms, the best surgical approach should be selected according to the aneurysmal height and fundus projection, and great care should be taken during surgery to minimize brain retraction and to prepare the hA, HA, and Al perforators.